2021
DOI: 10.3390/gases1040013
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Volumetric Flow Rate Requirement of Hydrogen Transportation in Existing Natural Gas Pipelines and Its Safety Implications

Abstract: As an alternative to the construction of new infrastructure, repurposing existing natural gas pipelines for hydrogen transportation has been identified as a low-cost strategy for substituting natural gas with hydrogen in the wake of the energy transition. In line with that, a 342 km, 36″ natural gas pipeline was used in this study to simulate some technical implications of delivering the same amount of energy with different blends of natural gas and hydrogen, and with 100% hydrogen. Preliminary findings from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…By mixing ammonia into NG, the compression factor, LHV, and WI are reduced. The compression factor is an important parameter in the flow of gases through pipes, where a too big variation in the compressibility factor can be a challenge for the media flowing in the pipeline 49 . When ammonia was added into the different NG compositions, the change in compression factor was minor and it is not a concern for the investigated cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By mixing ammonia into NG, the compression factor, LHV, and WI are reduced. The compression factor is an important parameter in the flow of gases through pipes, where a too big variation in the compressibility factor can be a challenge for the media flowing in the pipeline 49 . When ammonia was added into the different NG compositions, the change in compression factor was minor and it is not a concern for the investigated cases.…”
Section: Resultsmentioning
confidence: 99%
“…The compression factor is an important parameter in the flow of gases through pipes, where a too big variation in the compressibility factor can be a challenge for the media flowing in the pipeline. 49 When ammonia was added into the different NG compositions, the change in compression factor was minor and it is not a concern for the investigated cases. Instead, the decrease in the LHV with addition of ammonia can be a concern, since a bigger volume flow is needed to keep the same energy content as the original gas.…”
Section: Relative Densitymentioning
confidence: 97%
“…Simulations of velocity profiles in blended HCNG fuels have revealed that hydrogen may be safely blended up to 40% by volume. Once the hydrogen content increases above 40%, the erosional velocity limit is met for most pipeline materials and transportation of blended fuel above this concentration can become unsafe for most applications 36 . The gas compressibility factor ( z ), which changes based on the percentage of H 2 in the HCNG blended fuel, is also relevant.…”
Section: Operating Conditionsmentioning
confidence: 99%
“…Previous literature has extensively examined the performance impacts of injecting hydrogen into the natural gas transmission pipelines (Schouten 2004;Blacharski et al 2016;Witkowski et al 2018;Zabrzeski et al 2019;Kuczyński et al 2019;Abbas et al 2021). Just as mixture thermodynamic and transport properties discussed in Section 2 change with increasing blends of hydrogen, so do pipeline operating conditions.…”
Section: Pipeline Transportmentioning
confidence: 99%
“…Erosional velocity also increases for less-dense gas mixtures; as a result, this velocity is not approached in constant volume flow rate scenarios where hydrogen content increases (American Society of Mechanical Engineers 2019). This constraint may be relevant for maintaining energy delivery via increasing gas flow rates, because increased pressure drop along the pipeline will lead to increased gas velocities (Abbas et al 2021). Erosional velocity constraints may also be relevant for constant pressure drop operation, because the increase in volumetric flow rate with hydrogen concentration for constant pressure drop scenarios seen in Bainier and Kurz (2019) could only be achieved via an increase in flow velocity.…”
Section: Pipeline Transportmentioning
confidence: 99%